ANALISIS KEPATUHAN JADWAL PERMINTAAN LOGISTIK UMUM TERHADAP EFISIENSI DISTRIBUSI BARANG DI RS X - Evindasari; Enny Mar’atus Sholihah (Rena Cipta Mandiri, 2026)
Logistics management is an important component in supporting hospital operational activities. Logistics requests that do not follow the scheduled system can disrupt the distribution process and reduce the efficiency of logistics services. This study aims to analyze compliance with the schedule of general logistics requests and its impact on the efficiency of goods distribution at RS X. This research used a descriptive qualitative method with observation and problem analysis using the USG (Urgency, Seriousness, Growth) method. Data were obtained through field practice activities in the General Logistics Unit by observing the process of requesting and distributing logistics goods. The results showed that several work units still submitted logistics requests outside the predetermined schedule stated in the standard operating procedures, which disrupted the workflow of logistics staff, increased workload, and reduced the efficiency of the distribution process. The study concludes that compliance with logistics request schedules significantly influences the efficiency of goods distribution in hospitals. Therefore, it is necessary to improve SOP socialization, conduct periodic monitoring, and strengthen coordination between work units and the logistics department to enhance the effectiveness of hospital logistics management.